USM VC - OFFICIAL EDUCATION VISIT TO INDIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 15 November 2016 The Universiti Sains Malaysia (USM) ViceChancellor (VC), Professor Datuk Dr. Asma Ismail will be going to India for an official education visit to strengthen the collaboration and networking exercise among institutions there.